A Short Note on the Susceptibility in the Paramagnetic State for Disordered Itinerant-Electron Metamagnetic Materials - M. A. Grado-Caffaro; M. Grado-Caffaro (Active and Passive Electronic Components)
A formulation for the paramagnetic susceptibility of a typical disordered itinerant-electron metamagnetic material is proposed by using a tight-binding approximation. Moreover, some considerations on the susceptibility tensor are exposed.